Caffeine Citrate for Apnea of Prematurity: A Prospective, Open-Label, Single-Arm Study in Chinese Neonates - Du, Lizhong; Tong, Xiaomei; Chen, Chao; Gao, Xirong; Gagnatelli, Alessandra; Li, Jingyang; Santoro, Debora; Nicolardi, Sara; Fabbri, Laura; , The Peyona Chinese Study Group (Frontiers in Pediatrics, 2020)
Background Caffeine citrate has been approved in China for the management of apnea of prematurity. This clinical trial was conducted as a condition of regulatory approval. The aim was to confirm the efficacy of caffeine citrate in the treatment of recurrent intermittent hypoxia and bradycardia in preterm newborns with primary apnea. Objectives The primary outcome was the change from baseline in the number of apnea events after loading dose administration of caffeine citrate. Secondary efficacy outcomes included the change from baseline in apnea events after two and four weeks of maintenance doses. Methods This was a multicenter, prospective longitudinal open-label, single-arm study. Neonates who had experienced at least four apnea events during a 24h period received a loading dose of caffeine citrate 20mg/kg; those who required additional maintenance doses received 5mg/kg/day (titrated up to 10mg/kg/day in case of insufficient response). The number of apnea events was recorded for 6–12h prior to the loading dose (baseline), and for 12h post-dose, following the loading dose and at Weeks 2 and 4 (during maintenance). Results A total of 247 neonates received the loading dose, who had a significant reduction from baseline of 3.9 events (p<0.001) in the mean number of apnea events. The subset of neonates who required maintenance doses also had significant reductions in the number of events at all visits (p<0.001 for all). A total of 79.4% of participants had at least one adverse event, but only one non-serious and no serious events were considered related to treatment. Conclusions In this large, prospective, open-label study, premature infants with a history of apnea who received caffeine citrate were significantly less likely to experience further apnea events.